Reconstructing the Likelihood of Confusion Parameter in Indonesia’s First-to-File System: A Comparative Legal Analysis (EUIPO and USPTO) - Lanang Febria Galing; Afriansyah Tanjung (Universitas Dharmawangsa, 2026)
This study aims to reconstruct the likelihood of confusion parameters within Indonesia’s first-to-file trademark system. The main issue raised is the normative gap in Article 21 of the Trademark Law and Ministry of Law and Human Rights Regulation No. 67 of 2016 on Trademark Registration, which results in legal uncertainty and inconsistency in examiners decisions when assessing “substantial similarity.” This article employs doctrinal legal research using a comparative legal approach. The analysis compares Indonesian parameters with the EUIPO’s sequential test and the USPTO’s 13 DuPont factors. An emulation and hybridization approach is used to extract the best principles from both jurisdictions to design a new adaptive framework for Indonesia. The study found that the absence of a hierarchy for visual, phonetic, and conceptual assessments in Indonesian law creates excessive discretion that disadvantages applicants, particularly SMEs. Case studies of Y&N Skincare and LEGAWA Abon Gulung Premium demonstrate that vague parameters result in inconsistent rejections. Conversely, EUIPO and USPTO offer measurable and transparent assessment matrices. To strengthen legal certainty within the first-to-file system, Indonesia needs to transform the “substantial similarity” doctrine into a measurable likelihood-of-confusion parameter by hybridizing the European Union’s sequential test approach with the United States’ market-factor analysis. This restructuring is crucial for aligning national trademark registration practices with international protection standards.